Frequency of enamel defects and associated factors in 3 to 5-year-old children - Chambi Herrera, Karen Paola (2022)
Enamel defects are a set of clinically visible alterations in the enamel, due to disorders that occur during biomineralization or in the secretion of the enamel matrix. Primary teeth begin to form in the intrauterine stage and complete their development months after the birth of the child. During dental development, a series of factors are present which can affect ameloblastic function and lead to the development of enamel defects. Objective: To determine the frequency of enamel defects and associated factors in children from 3 to 5 years of age at Colegio Enrique Nerini (Lima) and Colegio María Inmaculada (Iquitos). Materials and methods: An observational, descriptive, cross-sectional, prospective study. The method was the survey and structured observation. The results were presented in tables of descriptive summary measures for the qualitative variables. For the bivariate analysis, the chi square test was used. Results: 340 children in deciduous dentition who met the inclusion criteria were evaluated, 170 children from each school. The total frequency of enamel defects was 3.6% (6), at the Enrique Nerini school (Lima). When evaluating the frequency of enamel defects at the María Inmaculada School (Iquitos), a frequency of enamel defects of 20.6% was found (35). Conclusions: The populations studied in both schools presented a low frequency of enamel defects, the frequency being higher in the María Inmaculada School.